2018
DOI: 10.1556/204.2018.40.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Controlling in Hungarian hospitals: History and key issues

Abstract: The aim of this review paper is to illustrate the areas of interest and the thinking of Hungarian hospital managers by providing a summary of the relevant Hungarian health care controlling literature and to give an introduction of potential research directions. The paper summarizes the “public discourse” and thinking on controlling, and simultaneously highlights the priorities of health care as well. The main range of interest are the financing problems and their solutions, as well as other kind of uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…A crucial step in the determination of health care costs has been the calculation of treatment costs of different diseases. This was an extremely difficult task, as the current Hungarian health care monitoring system is not able to provide the necessary data [ 81 ]. Therefore, we applied a successive strategy to estimate the costs of treatment: (1) When data for Hungary were available in the literature, we adopted them, but converted the original data to 2019 price levels, taking into consideration the official rates of inflation of the Hungarian National Bank (MNB, 2013).…”
Section: Methodology and Datamentioning
confidence: 99%
“…A crucial step in the determination of health care costs has been the calculation of treatment costs of different diseases. This was an extremely difficult task, as the current Hungarian health care monitoring system is not able to provide the necessary data [ 81 ]. Therefore, we applied a successive strategy to estimate the costs of treatment: (1) When data for Hungary were available in the literature, we adopted them, but converted the original data to 2019 price levels, taking into consideration the official rates of inflation of the Hungarian National Bank (MNB, 2013).…”
Section: Methodology and Datamentioning
confidence: 99%
“…A rendszer viszont nagyon gyakran formális marad, aminek Baran (2013) többek között a következő okokat tulajdonította: az integrált informatikai rendszerek elmaradottak, a dolgozók tudása és a menedzsment információja hiányos, valamint alacsony a közfinanszírozás. A hazai kórházi controllingrendszert egy korábbi szakirodalmi áttekintésben (Krenyácz, 2018a) részletesen bemutattam, de a legfontosabb ismérveket kiemelem. A leghangsúlyosabb a pénzügyi szemlélet, melynek középpontjában a likviditás és adósságkezelés áll, legfontosabb feladatának pedig az ellátásért elérhető finanszírozás maximalizálását és a szállítói állományok optimalizálását tekinti.…”
Section: Vezetéstudomány / Budapest Management Reviewunclassified
“…Korábbi kutatásaim alkalmával a hazai egészségügyi controllingrendszereket vizsgáltam meg (Krenyácz, 2015(Krenyácz, , 2017(Krenyácz, , 2018a, melyekben a controller munkáját is érintettem, de nem fejtettem ki bővebben funkcióját, szerepét és elfogadottságát. A hazai controllingkutatás szerint (Szukits, 2016) a vezetők inkább a számok előállítójaként tekintenek a controllerre, igaz ez az egészségügyben is.…”
Section: Konklúzió éS Kitekintésunclassified
“…Until the late 2000s, most hospitals were maintained by local governments. Starting in 2010, ownership was gradually transferred to the central state, with a new supervising agency established in 2012(Hajnal & Rosta, 2016) Recent qualitative research(Krenyácz, 2017), however, showed that centralization has not resulted in stricter adherence to budgetary limits.3 At least, not in the area of AMI care, or emergency care in general. Some specialties, like gynecology or elective surgical care, are operated as a mixture of private and public care, and may also be characterized by informal payments, where personal gains of physicians may also come into play.…”
mentioning
confidence: 99%